Preparation method and oil-water separation application of SiO2 NWs composite TPU material
By introducing prepared silica nanowires in thermoplastic polyurethane (TPU), SiO2 NWs/TPU composite materials were prepared by thermally induced phase separation method, the problems of insufficient mechanical durability and environmental adaptability of existing materials were solved, and super-enabled Hydrophobicity, super lipophilicity and excellent oil-water separation properties.
Patent Information
- Application Number
- CN202411779184.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-11
AI Technical Summary
The application of existing superhydrophobic materials in the field of oil-water separation is limited by insufficient mechanical durability and environmental adaptability, and the improvement of hydrophobic properties of traditional nanomaterials requires multiple modification processes, which is time-consuming and labor-intensive.
Silica nanowires were prepared by sol-gel method and introduced into thermoplastic polyurethane (TPU) by heat-induced phase separation method to form SiO2 NWs/TPU composite material to achieve superhydrophobicity, super lipophilicity and mechanical properties of the material. Durability and environmental adaptability.
The prepared SiO2 NWs/TPU composite material has excellent oil-water separation performance, good mechanical properties and environmental stability, and is suitable for oil-water separation applications in harsh environments.
Smart Images

Figure CN119406386A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional material preparation, and specifically relates to a preparation method of a SiO2 NWs composite TPU material and its oil-water separation application. Background Art
[0002] With the development of society and industry, people's demand for oil is increasing. However, oil leakage has become a global problem that urgently needs to be solved [1,2]. Traditional oil removal technologies include skimmer collection, combustion, and biological treatment, but these methods are often accompanied by high costs, secondary pollution, low efficiency, and other problems [3-5]. Among them, the adsorption method has attracted widespread attention due to its advantages such as low cost, simple operation, and environmental protection [6-8]. In recent years, many researchers have developed adsorption materials with unique wetting properties, such as aerogels, microspheres, cotton fabrics, polymer foams, etc. [9-12]. However, poor mechanical durability and environmental adaptability are key factors affecting the life of materials, which greatly limit the large-scale application of superhydrophobic materials in the field of oil-water separation. Therefore, how to improve the mechanical durability and environmental adaptability of materials has always been the focus of research.
[0003] As a type of porous polymer monomer, thermoplastic polyurethane (TPU) has excellent resilience and mechanical strength
[13] . However, the water contact angle of pure TPU is much less than 150°, and it cannot be used on the sea surface. In order to solve this problem, some researchers have added nanomaterials and adopted a blending modification method to improve the hydrophobicity and enhance the mechanical strength and environmental adaptability [14-16]. However, the nanomaterials commonly used in blending modification are hydrophilic materials, and it is necessary to modify the hydrophobic groups to improve their hydrophobic properties and then improve the mechanical durability of TPU. This method is time-consuming and labor-intensive [17-19]. At present, how to use TPU to manufacture high-performance materials through a one-step method is still a challenge. Therefore, it is of great practical significance to efficiently and quickly prepare materials with super hydrophobicity, super oleophilicity, excellent mechanical durability and environmental adaptability.
[0004] References
[0005] [1] CL Chen, D. Weng, A. Mahmood, et al. Separation mechanism and construction of surfaces with special wettability for oil / water separation [J]. ACS Applied Materials&Interfaces, 2019, 11(11): 11006-11027.
[0006] [2]L.Han,C.Chen,L.G.Shen,et al.Novel membranes with extremely highpermeability fabricated by 3D printing and nickel coating for oil / waterseparation[J].Journal ofMaterials Chemistry A,2022,10(22):12055-12061.
[0007] [3]H.Wen,L.Z.Liang,N.Y.Xu,et al.Multi-functional self-cleaningsuperhydrophobic cotton fabric as photothermal-reinforced crude oilseparator,oil skimmer and underwater oil absorbent[J].SeparationandPurification Technology,2024,337:126258.
[0008] [4]G.F.John,Y.Han,T.P.Clement.Fate of hopane biomarkers during in-situ burning of crude oil—a laboratory-scale study[J].MarinePollutionBulletin,2018,133:756-761.
[0009] [5]Y.H.Zhang,J.J.Xu,X.Q.Jiang,et al.Selective absorption andefficient biodegradation of petroleum pollutants by oleophilic porousactivated sludge loading with microorganism[J].Journal of EnvironmentalChemicalEngineering,2023,11(1):109005.
[0010] [6]S.Rasouli,N.Rezaei,H.Hamedi,et al.Superhydrophobic andsuperoleophilic membranes for oil-water separation application:acomprehensive review[J].Materials&Design,2021,204:109599.
[0011] [7]H.N.Duan,H.H.Lyu,B.X.Shen,et al.Superhydrophobic-superoleophilicbiochar-based foam for high-efficiency and repeatable oil-water separation[J].Science ofThe Total Environment,2021,780:146517.
[0012] [8]W.Zhang,Y.Liu,F.Tao,et al.An overview ofbiomass-based Oil / Waterseparation materials[J].Separation andPurification Technology,2023,316:123767.
[0013] [9]Y.Bao,J.X.Chang,Y.X.Zhang,et al.Robust superhydrophobic coatingwith hollow SiO2 / PAA-b-PS Janus microspheres for self-cleaning and oil-waterseparation[J].ChemicalEngineering Journal,2022,446:136959.
[0014]
[10] Y.C.Li,Z.Y.Lin,X.Y.Wang,et al.High-hydrophobic ZIF-8@PLAcomposite aerogel and application for oil-water separation[J].SeparationandPurification Technology,2021,270:118794.
[0015]
[11] Y.Q.Dong,W.B.Bai,W.Zhang,et al.Bio-based phytic acid@polyurushiol-titanium complex coated cotton fabrics with durable flameretardancy for oil-water separation[J].International Journal ofBiologicalMacromolecules,2023,235:123782.
[0016]
[12] H.L.Yang,G.H.Xu,J.T.Li,et al.Fabrication ofbio-basedbiodegradable poly(lactic acid)(PLA)andpoly(3-hydroxybutyrate-co-3-hydroxyvalerate)(PHBV)composite foams for highly efficient oil-waterseparation[J].InternationalJournalofBiologicalMacromolecules,2024,257:128750.
[0017]
[13] X.Z.Lü,T.T.Yu,F.C.Meng,et al.Wide-range and high-stabilityflexible conductive graphene / thermoplastic polyurethane foamforpiezoresistive sensor applications[J].AdvancedMaterials Technologies,2021,6(10):2100248.
[0018]
[14] Z.He,J.H.Byun,G.H.Zhou,et al.Effect of MWCNT content on themechanical and strain-sensing performance of thermoplastic polyurethanecomposite fibers[J].Carbon,2019,146:701-708.
[0019]
[15] J.R.Gouveia,R.R.E Sousa,A.O.Ribeiro,et al.Effect ofsoft segmentmolecular weight and NCO:OH ratio on thermomechanical properties oflignin-based thermoplastic polyurethane adhesive[J].EuropeanPolymerJournal,2020,131:109690.
[0020]
[16] S.Y.Li,F.Qiu,Y.G.Xia,et al.Integrating a self-floatingjanus TPC@CB sponge for efficient solar-driven interfacial water evaporation[J].ACSApplied Materials&Interfaces,2022,14(17):19409-19418.
[0021]
[17] Y.T.Shi,B.Wang,S.H.Ye,et al.Magnetic,superelastic andsuperhydrophobic porous thermoplastic polyurethane monolith with nano-Fe3O4coating for highly selective and easy-recycling oil / waterseparation[J].AppliedSurfaceScience,2021,535:147690.
[0022]
[18] J.L.Wu,X.Z.Ma,P.Gnanasekar,et al.Superhydrophobic lignin-basedmultifunctional polyurethane foam with SiO2 nanoparticles for efficient oiladsorption and separation[J].Science ofThe TotalEnvironment,2023,860:160276.
[0023]
[19] S.Liu,SSWang,H.Wang,et al.Gold nanoparticles modified graphenefoam with superhydrophobicityandsuperoleophilicity for oil-water separation[J].Science ofThe TotalEnvironment,2021,758:143660.
[0024] Invention patent content
[0025] The purpose of the present invention is to provide a method for preparing a material with simple process, safe operation, excellent oil-water separation performance, good mechanical durability and environmental adaptability. The thermally induced phase separation method is used to introduce silica nanowires into TPU to form a new micro-nano structure and pore structure. The prepared composite material has the advantages of super hydrophobicity, super oleophilicity, excellent mechanical durability and environmental adaptability, and has good application prospects.
[0026] In order to achieve the above purpose, the present invention adopts the following technical solution: the preparation method of the SiO2 NWs composite TPU material and the oil-water separation application, characterized in that the specific steps are as follows:
[0027] (1) Preparation of silica nanowires by sol-gel method: First, polyvinyl pyrrolidone (PVP) and an alcohol solvent were ultrasonically mixed for 2 hours; then, deionized water, sodium citrate solution and ammonia water were added and oscillated to ensure a uniform solution. Next, a silicon source and a long-chain silane were added and oscillated to mix for 12 hours. After the reaction was completed, the reaction product was washed with an appropriate solvent (anhydrous ethanol or deionized water) to remove unreacted substances and impurities, and finally SiO2 nanowires were obtained.
[0028] (2) Preparation of SiO2 NWs / TPU composites by thermally induced phase separation: TPU and SiO2 NWs were dissolved in a mixed solvent consisting of 1,4-dioxane and deionized water. The solution was placed in an ice-water bath for 30 min and then transferred to a refrigerator to freeze (-20°C, 48 h) until the sample was completely freeze-dried. Finally, the ice tube was placed in a freeze dryer (-50°C, 72 h) to obtain a SiO2 NWs / TPU composite.
[0029] (3) In step (2), the concentration (wt / v) of TPU is 4% to 12%;
[0030] The mass ratio of TPU to SiO2 NWs is 3:1 to 20:1;
[0031] The mixed solvent ratio of 1,4-dioxane and deionized water is 9:1 to 20:1;
[0032] The phase separation temperature is -10 to 4°C;
[0033] The phase separation time is 5 to 720 minutes;
[0034] The refrigerator freezing time is 24 to 72 hours (depending on the sample quantity);
[0035] The freeze drying conditions are: cold trap temperature -50°C, vacuum degree less than 50Pa, time 24 to 72h (depending on the sample amount);
[0036] Furthermore, the super-hydrophobic and super-oleophilic composite material is prepared by the method described in any one of claim 1;
[0037] Furthermore, the superhydrophobic and superoleophilic composite material is a composite material obtained by thermally induced phase separation of silica nanowires and thermoplastic polyurethane;
[0038] Furthermore, the super-hydrophobic and super-oleophilic composite material can be used in the recovery of leaked oil products and the separation of oil-water mixtures in harsh environments such as high temperature, strong acid and strong alkali; the oil is a mixture of one or more of crude oil, diesel, gasoline, lubricating oil, edible oil, hexane, toluene, ethylbenzene, and dichloromethane;
[0039] Furthermore, the oil-water separation application may adopt a static adsorption mode or a continuous adsorption mode. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 SEM images of SiO2 NWs after the introduction of TPU at different concentrations (a2) 0.25%, (a3) 0.5%, (a4) 1%, (a5) 2%;
[0041] Figure 2 The water contact angle after introducing TPU at different concentrations;
[0042] Figure 3 The oil-water separation performance of SiO2 NWs / TPU composites. SiO2 NWs / TPU was used to separate (a) vegetable oil and (b) chloroform (the vegetable oil and chloroform were dyed red for observation);
[0043] Figure 4Compressive mechanical properties of SiO2 NWs / TPU composites. (a) Compressive stress-strain curve (the inset shows the compression process); (b) Compressive stress-strain curve of SiO2 NWs / TPU under different compression times (the inset shows the change of SiO2 NWs / TPU before and after 100 compressions);
[0044] Figure 5 The environmental adaptability performance test diagram of SiO2 NWs / TPU composite materials. (a) Water contact angle of SiO2 NWs / TPU under mechanical wear (the inset is a schematic diagram of the mechanical wear experiment and the water contact angle under different wear times); (b) Change of water contact angle of SiO2 NWs / TPU after heating at 200°C (the inset is a schematic diagram of the water contact angle after different heating times); (c) Water contact angle of SiO2 NWs / TPU after boiling water treatment (the inset is the water contact angle after different boiling water times);
[0045] Figure 6 This is the chemical stability test diagram of SiO2 NWs / TPU composite materials;
[0046] Figure 7 Pump-assisted continuous adsorption performance of SiO2 NWs / TPU composite materials; (a) Continuous oil-water separation device using SiO2 NWs / TPU; (b) Separation of vegetable oil and water; (c) Oil and clear water collected after separation (the vegetable oil is dyed red for observation). DETAILED DESCRIPTION
[0047] The present invention will be further described below in conjunction with the accompanying drawings and embodiments, so that the above contents can be better understood. Figure 1 , 2, 3, 4, 5, 6, 7 are the results of Example 1.
[0048] Example 1: 40.0 g of polyvinyl pyrrolidone (PVP, Mw 4000) was added to 400.0 mL of n-pentanol and ultrasonically treated for 2 hours until completely dissolved. Subsequently, 40.0 mL of ethanol, 11.2 mL of deionized water and 2.68 mL of sodium citrate solution (0.18 M aqueous solution) were added, and a mechanical stirrer was used to stir at 1800 rpm for 5 minutes to ensure uniform mixing. Next, 8.0 mL of ammonia water was added and continued to stir at a speed of 1800 rpm for 2 minutes. Then, 4.0 mL of tetraethoxysilane (TEOS) and 0.4 mL of octadecyltrimethoxysilane (C18TMOS) were added and continued to stir at a speed of 1800 rpm for 2 minutes to ensure uniform reaction. After the reaction was completed, the sample was allowed to stand for 12 hours to complete the reaction. Next, the product was dispersed in water and freeze-dried by centrifugation and washing with an appropriate solvent to obtain silica nanowires (SiO2 NWs). In order to prepare SiO2 NWs / TPU composites, SiO2 nanowires and thermoplastic polyurethane (TPU) were dissolved in a mixed solvent of 1,4-dioxane and deionized water with a mixed solvent ratio of 9:1. The resulting solution was cooled at 0°C for 30 minutes and then transferred to a refrigerator at -20°C for 48 hours to ensure sufficient freeze-drying. Finally, the frozen sample was placed in a freeze dryer and freeze-dried at -50°C for 72 hours to obtain the SiO2 NWs / TPU composite.
[0049] The scanning electron microscope images of SiO2NWs / TPU obtained by introducing different mass fractions of silicon dioxide nanowires prepared in this example into TPU are shown in FIG. Figure 1 The water contact angle after introducing TPU with different mass fractions is shown in Figure 2 ,from Figure 1 As can be seen from Figure 2, in this embodiment, compared with the TPU substrate or SiO2 NWs / TPU without or with low concentration of SiO2 NWs, it can be clearly seen that the SiO2NWs / TPU composite material with high concentration of SiO2 NWs contains a large amount of SiO2 NWs, indicating that the silica nanowires are successfully assembled and loaded inside the TPU. When the mass fraction of the silica nanowire solution reaches 2.4%, the water contact angle of the composite material is as high as 158°, achieving super hydrophobic performance.
[0050] The SiO2 NWs / TPU obtained by introducing the 2.4% mass fraction of silica nanowire solution prepared in this embodiment into TPU has excellent oil-water separation performance, compression performance and environmental adaptability. SiO2 NWs / TPU is used to separate vegetable oil (a) and chloroform (b), and the vegetable oil and chloroform are dyed red for observation. When in contact with the vegetable oil floating on the surface, the SiO2 NWs / TPU quickly absorbs the oil and cleans the water. In addition, when the SiO2 NWs / TPU is immersed in the bottom of the CCl4 / water mixture and approaches CCl4, it quickly absorbs CCl4, and there are no CCl4 droplets in the water. The compression performance test of SiO2 NWs / TPU is shown in Figure 4 , which shows the compressive stress-strain curve of SiO2 NWs / TPU under different compression times. It can be observed that the material has good reversible compressibility at 80% strain. After 100 cycles, the compressive strength of SiO2 NWs / TPU composite material only decreased slightly (<130kPa), and still achieved a high compression performance of 467kPa. Environmental adaptability performance test of SiO2 NWs / TPU can be seen in Figure 5 , which showed that SiO2 NWs / TPU was baked in an oven at 200℃ and boiled in boiling water at 100℃ for 24h ( Figure 5 b, c) Changes in water contact angle. Although the hydrophobicity has decreased (<7°), it still maintains superhydrophobicity, and its water contact angles are 150.9° and 153.1°, respectively, indicating that the composite material has excellent environmental stability. It shows that SiO2 NWs / TPU has superhydrophobicity and superoleophilicity, excellent compressibility and environmental adaptability.
[0051] Example 2: 40.0 g of polyvinyl pyrrolidone (PVP, Mw 4000) was added to 400.0 mL of n-pentanol and ultrasonically treated for 2 hours until completely dissolved. Subsequently, 40.0 mL of ethanol, 11.2 mL of deionized water and 2.68 mL of sodium citrate solution (0.18 M aqueous solution) were added, and a mechanical stirrer was used to stir at 1800 rpm for 5 minutes to ensure uniform mixing. Next, 8.0 mL of ammonia water was added and continued to stir at a speed of 1800 rpm for 2 minutes. Then, 4.0 mL of tetraethoxysilane (TEOS) and 0.4 mL of octadecyltrimethoxysilane (C18TMOS) were added and continued to stir at a speed of 1800 rpm for 2 minutes to ensure uniform reaction. After the reaction was completed, the sample was allowed to stand for 12 hours to complete the reaction. Next, the product was dispersed in water and freeze-dried by centrifugation and washing with an appropriate solvent to obtain silica nanowires (SiO2 NWs). In order to prepare SiO2 NWs / TPU composites, SiO2 nanowires and thermoplastic polyurethane (TPU) were dissolved in a mixed solvent of 1,4-dioxane and deionized water with a mixed solvent ratio of 9:0.5. The resulting solution was cooled at 7°C for 30 minutes and then transferred to a refrigerator at -20°C for 48 hours to ensure sufficient freeze-drying. Finally, the frozen sample was placed in a freeze dryer and freeze-dried at -50°C for 72 hours to obtain the SiO2NWs / TPU composite.
[0052] Example 3: 40.0 g of polyvinyl pyrrolidone (PVP, Mw 4000) was added to 400.0 mL of n-pentanol and ultrasonically treated for 2 hours until completely dissolved. Subsequently, 40.0 mL of ethanol, 11.2 mL of deionized water and 2.68 mL of sodium citrate solution (0.18 M aqueous solution) were added, and a mechanical stirrer was used to stir at 1800 rpm for 5 minutes to ensure uniform mixing. Next, 8.0 mL of ammonia water was added and continued to stir at a speed of 1800 rpm for 2 minutes. Then, 4.0 mL of tetraethoxysilane (TEOS) and 0.4 mL of octadecyltrimethoxysilane (C18TMOS) were added and continued to stir at a speed of 1800 rpm for 2 minutes to ensure uniform reaction. After the reaction was completed, the sample was allowed to stand for 12 hours to complete the reaction. Next, the product was dispersed in water and freeze-dried by centrifugation and washing with an appropriate solvent to obtain silica nanowires (SiO2 NWs). In order to prepare SiO2 NWs / TPU composites, SiO2 nanowires and thermoplastic polyurethane (TPU) were dissolved in a mixed solvent of 1,4-dioxane and deionized water with a mixed solvent ratio of 18:1. The resulting solution was cooled at 7°C for 30 minutes and then transferred to a refrigerator at -20°C for 48 hours to ensure sufficient freeze-drying. Finally, the frozen sample was placed in a freeze dryer and freeze-dried at -50°C for 72 hours to obtain the SiO2NWs / TPU composite.
[0053] It should be emphasized that the above description only represents several preferred embodiments of the present invention and does not constitute a limitation on the scope of protection of the present invention. Although these embodiments are described in detail in this specification, professionals in this field should understand that the technical solutions disclosed in the above embodiments can be adjusted or modified, and some technical features can be replaced by equivalents without departing from the core concept and basic principles of the present invention. Any improvement, optimization, equivalent replacement, etc. made within the creative concept and theoretical framework of the present invention should be regarded as part of the scope of protection of the present invention.
Claims
1. A preparation method of SiO2 NWs composite TPU material and its application in oil-water separation, characterized in that: The specific steps are as follows: (1) Preparation of silica nanowires by sol-gel method: First, polyvinyl pyrrolidone (PVP) and an alcohol solvent were ultrasonically mixed for 2 hours; then, deionized water, sodium citrate solution and ammonia water were added and oscillated to ensure a uniform solution. Next, a silicon source and a long-chain silane were added and oscillated to mix for 12 hours. After the reaction was completed, the reaction product was washed with an appropriate solvent (anhydrous ethanol or deionized water) to remove unreacted substances and impurities, and finally SiO2 nanowires were obtained. (2) Preparation of SiO2 NWs / TPU composites by thermally induced phase separation: TPU and SiO2 NWs were dissolved in a mixed solvent consisting of 1,4-dioxane and deionized water. The solution was placed in an ice-water bath for 30 min to achieve phase separation, and then transferred to a refrigerator to freeze (-20°C, 48 h) until the sample was completely freeze-dried. Finally, the ice tube was placed in a freeze dryer (-50°C, 72 h) to obtain a SiO2 NWs / TPU composite. (3) In step (2), the concentration (wt / v) of TPU is 4% to 12%; The mass ratio of TPU to SiO2 NWs is 3:1 to 20:1; The mixed solvent ratio of 1,4-dioxane and deionized water is 9:1 to 20:1; The phase separation temperature is -10 to 4°C; The phase separation time is 5 to 720 minutes; The refrigerator freezing time is 24 to 72 hours (depending on the sample quantity); The freeze-drying conditions are: cold trap temperature -50°C, vacuum degree less than 50Pa, and time 24 to 72 hours (depending on the sample amount).
2. The preparation method and oil-water separation application of a SiO2 NWs composite TPU material according to claim 1, characterized in that: The super-hydrophobic and super-oleophilic composite material is prepared by the method described in any one of claim 1.
3. The preparation method and oil-water separation application of a SiO2 NWs composite TPU material according to claim 1, characterized in that: The superhydrophobic and superoleophilic composite material is a composite material obtained by thermally induced phase separation of silica nanowires and thermoplastic polyurethane.
4. The preparation method and oil-water separation application of a SiO2 NWs composite TPU material according to claim 1, characterized in that: The super-hydrophobic and super-oleophilic composite material can be used in the recovery of leaked oil and the separation of oil-water mixtures in harsh environments such as high temperature, strong acid and strong alkali; the oil is a mixture of one or more of crude oil, diesel, gasoline, lubricating oil, edible oil, hexane, toluene, ethylbenzene, and dichloromethane.
5. The preparation method and oil-water separation application of a SiO2 NWs composite TPU material according to claim 1, characterized in that: The oil-water separation application may adopt a static adsorption mode or a continuous adsorption mode.